Lentinan-Based Oral Nanoparticle Loaded Budesonide With Macrophage-Targeting Ability for Treatment of Ulcerative Colitis - Lin, Meisi; Dong, Lingling; Chen, Qiyan; Xu, Haiting; Han, Xiaoqin; Luo, Ruifeng; Pu, Xiulan; Qi, Shanshan; Nie, Wenbiao; Ma, Meilin; Wang, Yitao; Gao, Fei; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Ulcerative colitis (UC) is a global, chronic and refractory disease. Corticosteroids are first-line drugs for the treatment of UC but also cause adverse sid e effects. Budesonide (BUD), a corticosteroid with relatively low side effects, has been approved by the Food and Drug Administration for use as enteric capsules (Entocort EC) for the treatment of inflammatory bowel disease (IBD). However, this formulation lacks specific targeting ability to UC lesions. Herein, we describe the development of an advanced macrophage-targeted oral lentinan (LNT)-based nanoparticle (NPs) loaded BUD for treatment of UC. Briefly, LNT was used as a food-source and natural carrier to load BUD by a simple solvent evaporation method to form LNT/BUD-NPs. LNT showed good loading capacity with high encapsulation and loading efficiencies to BUD of approximately 92.19% and 9.58% respectively. Evaluation of the gastric stability of LNT/BUD-NPs indicated that LNT could effectively protect BUD from gastric acid and digestive enzymes. The release behavior and Transmission Electron Microscopy image of LNT/BUD-NPs in the intestinal content of mice confirmed that intestinal flora can promote BUD release from LNT. Moreover, evaluation of cellular uptake showns that LNT/BUD-NPs could specifically target macrophages and enhance their uptake rate via the Dectin-1 receptor. In biodistribution studies, LNT/BUD-NPs were able to efficiently accumulate in the inflamed colon of mice. As expected, LNT/BUD-NPs could significantly alleviate inflammation by inhibiting the TLR4/MyD88/NF-κB signaling pathway. Therefore, LNT/BUD-NPs have the advantages of good gastric stability, release mediated by mouse intestinal content, macrophage-targeting, and anti-UC effects. These advantages indicate LNT-based NPs are a promising oral drug delivery system for UC therapy.